Medical problems of working at altitudes of 4000 - 5000 m - West, Jhon B. (Acta Andina, 2025)
Recently there have been increasing commercial activities at altitudes of 4000-5000 m, for example new mines in north Chile. Because the workers come from sea level altitude intolerance is a major problem. This article addresses three areas: 1) Methods for selecting workers who can tolerate these high altitudes. 2) Optimal scheduling of time between the mine and the home at sea level. 3) Value of oxygen enrichment of room air in some parts of the mine. This last is remarkably effective. At these altitudes, each 1% increase in O2 concentration (e.g. from 21 to 22%) reduces the equivalent the altitude by about 300 m. Control of the oxygen concentration can be regarded as a further logical step in man’s control of his environment.